Graphite negative electrode material and preparation method thereof

CN121158774BActive Publication Date: 2026-10-20PETROCHINA CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410786243.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2026-10-20
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

[0009]本发明的主要目的在于提供一种石墨负极材料及其制备方法,以克服现有技术中包覆层包覆不均匀,负极材料倍率性能差等缺陷

Benefits of technology

[0024]本发明利用石墨微片的二维片层结构修饰改性针状焦基石墨,构筑富通道负极材料,可以增加储锂位点及传输通道,显著提升锂电池的倍率性能、快充性能以及循环性能。另外,本发明使用单宁酸对石墨微片改性石墨材料进行包覆,单宁酸可以将石墨和石墨微片牢牢地结合在一起,可以实现石墨微片与石墨负极的紧密结合;单宁酸在碳化后在石墨形成包覆层,可以提高其导电性、阻止电解液浸润石墨,抑制溶剂共嵌入从而防止石墨层脱落,有助于形成稳定的SEI膜以及长循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121158774B_ABST
    Figure CN121158774B_ABST
Patent Text Reader

Abstract

The application provides a graphite negative electrode material and a preparation method thereof, and comprises the following steps: step 1, mixing graphite microsheets, graphite and water, and ultrasonic treatment; step 2, mixing the mixture obtained in step 1 with a tannic acid solution, and then removing the solvent to obtain a graphite negative electrode material precursor; and step 3, carbonizing the graphite negative electrode material precursor to obtain the graphite negative electrode material. The application uses the two-dimensional sheet structure of the graphite microsheets to modify the needle coke-based graphite, constructs a channel-rich negative electrode material, can increase the lithium storage sites and transmission channels, and significantly improves the rate performance, fast charging performance and cycle performance of the lithium battery. In addition, the application uses tannic acid to coat the graphite microsheet modified graphite material, the coating layer is uniform and controllable, and the coating layer can form a good conductive network after carbonization, so that the negative electrode material has a high capacity, a clear and long charging and discharging platform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery anode materials, specifically to a graphite anode material and its preparation method. Background Technology

[0002] Graphite anode materials have become the mainstream anode material for lithium-ion batteries due to their good conductivity, chemical stability, low lithium storage potential, and low cost. Currently, artificial graphite anodes account for as much as 85% of lithium battery anode materials. However, existing graphite anode materials have limitations. First, their capacity is limited (not exceeding 360 mAh / g), their safety performance is generally poor, and their cost is increasing. Second, they have poor compatibility with organic solvents, easily leading to solvent co-intercalation and reducing lithium intercalation performance. Therefore, high capacity, long cycle life, and high safety are important research directions for graphite anode materials in lithium-ion batteries, and are of great significance to the development of power batteries.

[0003] Studies have found that the introduction of graphite microflakes significantly improves the capacity, cycle life, and safety performance of graphite anode materials. However, existing technologies typically introduce graphite oxide microflakes, which greatly increases costs and generates a large amount of waste acid during preparation, making it environmentally unfriendly. Therefore, using graphite oxide microflakes for modification makes it difficult to achieve large-scale production and application of graphite anode materials.

[0004] The method of modifying graphite anodes with graphite microplates is relatively simple, and the graphite microplates are low in cost, have good electrical and thermal conductivity, and are suitable for mass production. The resulting graphite anodes modified with graphite microplates will have significant improvements in capacity, cycle life, and safety performance.

[0005] CN116169273A describes a method that mixes a material with a liquid-phase coating agent, then with asphalt, and carbonizes it at high temperature to obtain a composite-coated precursor. This precursor is then subjected to sieving, depolymerization, and demagnetization to obtain a composite-coated artificial graphite anode material. While this method yields a coated graphite anode material, the double-layer coating may result in slow lithium-ion transport, leading to poor rate performance. Furthermore, the process is overly complex, uneconomical, environmentally unfriendly, and costly, making it unsuitable for industrial production.

[0006] CN113526956A places the material in fluidized asphalt at a temperature 40°C–50°C above the melting point of the asphalt. While ensuring the formation of a coating layer, it also ensures that the asphalt fills the internal voids of the graphite micropowder, increasing the material's compaction density. However, this inevitably improves cycling performance at the expense of the material's rate performance, and it's difficult to guarantee uniform coating and filling of the graphite in the fluidized asphalt. Although this method improves the cycling performance of the graphite anode to some extent, there is significant room for improvement in rate performance. Furthermore, this method is difficult to guarantee uniform product quality in industrial operations, which is detrimental to large-scale production.

[0007] CN115911304A describes a method that mixes isotropic graphite granules with a liquid-phase coating agent and performs a liquid-phase coating treatment, forming a liquid-phase organic coating layer on the surface of the isotropic graphite granules to obtain a pre-fabricated graphite anode material. The pre-fabricated graphite anode material is then carbonized, sieved, and demagnetized to obtain a liquid-phase coated graphite anode material. This method can obtain a coating layer of relatively uniform thickness, but it only improves cycle performance to a certain extent; the rate capability of the graphite anode material still needs to be improved.

[0008] Therefore, further research is needed on graphite anode materials in this field. Summary of the Invention

[0009] The main objective of this invention is to provide a graphite anode material and its preparation method, so as to overcome the defects of uneven coating and poor rate performance of anode materials in the prior art.

[0010] To achieve the above objectives, the present invention provides a method for preparing a graphite anode material, comprising the following steps:

[0011] Step 1: Mix graphite flakes, graphite, and water, and then sonicate.

[0012] Step 2: Mix the mixture obtained in Step 1 with a tannic acid solution, and then remove the solvent to obtain a graphite anode material precursor;

[0013] Step 3: Carbonize the graphite anode material precursor to obtain the graphite anode material.

[0014] The method for preparing the graphite anode material of the present invention, wherein in step 1, the mass ratio of graphite micro-flakes, graphite and water is (0.5-1.5):19:(80-120); the graphite is expanded graphite powder or flake graphite.

[0015] The method for preparing the graphite anode material according to the present invention, wherein the ultrasonic treatment time is 0.5h-2h.

[0016] The method for preparing graphite anode material according to the present invention, wherein the tannic acid solution is a solution formed by mixing tannic acid with a first solvent, wherein the first solvent is selected from organic solvents and inorganic solvents.

[0017] The method for preparing graphite anode material according to the present invention, wherein the organic solvent is ethanol or acetone; the inorganic solvent is water; and the ratio of the mass of tannic acid to the volume of the first solvent in the tannic acid solution is 1.5-4.5 g: 100 mL.

[0018] The method for preparing the graphite anode material of the present invention, wherein the mass ratio of graphite to tannic acid is 8:1-20:1.

[0019] The method for preparing the graphite anode material of the present invention includes a mixing time of 0.5-5 hours in step 2, during which stirring is performed.

[0020] The method for preparing the graphite anode material of the present invention, wherein the carbonization temperature is 900-1300℃ and the heating rate is 2-7℃ / min.

[0021] The method for preparing the graphite anode material of the present invention includes a method in which the graphite anode material precursor is first heated to 400-800°C and held for a period of time, and then heated to the carbonization temperature for carbonization.

[0022] To achieve the above objectives, the present invention also provides a graphite anode material obtained by the above preparation method.

[0023] The beneficial effects of this invention are:

[0024] This invention utilizes the two-dimensional layered structure of graphite microflakes to modify needle-shaped coke-based graphite, constructing a channel-rich anode material. This increases lithium storage sites and transport channels, significantly improving the rate performance, fast-charging performance, and cycle performance of lithium batteries. Furthermore, this invention uses tannic acid to coat the graphite material modified from graphite microflakes. Tannic acid firmly binds graphite and graphite microflakes together, achieving a tight bond between the graphite microflakes and the graphite anode. After carbonization, the tannic acid forms a coating layer on the graphite, improving its conductivity, preventing electrolyte wetting of the graphite, and inhibiting solvent co-intercalation, thereby preventing graphite layer detachment and contributing to the formation of a stable SEI film and long cycle performance. Attached Figure Description

[0025] Figure 1 The graph shows the rate performance of three materials prepared in Example 1 of this invention: graphite micro-flake modified graphite, commercial graphite anode material, and graphite raw material.

[0026] Figure 2 Charge-discharge curves for commercial graphite anode materials.

[0027] Figure 3 The charge-discharge curves of graphite raw materials are shown.

[0028] Figure 4 The charge-discharge curves of the graphite micro-sheet modified graphite negative electrode prepared in Example 1 of this invention are shown.

[0029] Figure 5 This is a scanning electron microscope image of the graphite microflakes modified with tannic acid after being prepared in Example 1.

[0030] Figure 6 The image shows a scanning electron microscope (SEM) image of the uncoated graphite flakes modified with graphite prepared in Comparative Example 2. Detailed Implementation

[0031] The technical solution of the present invention will be described in detail below. The following embodiments are implemented under the premise of the technical solution of the present invention and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following embodiments. Structures or experimental methods that do not specify specific conditions in the following embodiments are generally performed under conventional conditions.

[0032] This invention provides a method for preparing a graphite anode material, comprising the following steps:

[0033] Step 1: Mix graphite flakes, graphite, and water, and then sonicate.

[0034] Step 2: Mix the mixture obtained in Step 1 with a tannic acid solution, and then remove the solvent to obtain a graphite anode material precursor;

[0035] Step 3: Carbonize the graphite anode material precursor to obtain the graphite anode material.

[0036] This invention utilizes the two-dimensional layered structure of graphite microflakes to modify needle-shaped coke-based graphite, constructing a channel-rich anode material. This increases lithium storage sites and transport channels, significantly improving the rate performance, fast-charging performance, and cycle performance of lithium batteries. Furthermore, this invention uses tannic acid to coat the graphite material modified from graphite microflakes. Tannic acid firmly binds the graphite and graphite microflakes together, achieving a tight bond between the graphite microflakes and the graphite anode. After carbonization, the tannic acid forms a coating layer on the graphite, improving its conductivity, preventing electrolyte wetting of the graphite, and inhibiting solvent co-intercalation, thus preventing graphite layer detachment. This contributes to the formation of a stable SEI film and long cycle performance. The coating layer is uniform and controllable, and after carbonization, it forms a good conductive network, resulting in a cathode material with high capacity and a significant and long charge / discharge plateau.

[0037] This invention does not impose special requirements on graphite. Those skilled in the art can select appropriate graphite powder according to the needs of on-site operations. In specific embodiments of this invention, the graphite powder used includes expanded graphite and flake graphite.

[0038] This invention does not specifically limit the type of graphite microsheets; any graphite microsheet in the art is acceptable. In one embodiment, this invention provides a method for preparing graphite microsheets. Specifically, this method uses a supercritical CO2 fluid exfoliation method to prepare graphite microsheets. First, upon reaching a supercritical state (supercritical fluid temperature 50°C, pressure 8.5 MPa), due to the significantly enhanced diffusivity and permeability, CO2 fluid molecules intercalate into the graphite layers. Then, under high-speed rotation of the shearing blade (shearing speed 2200 r / min, time 45 min), a strong shearing force is generated between the fluid media. This force enhances the diffusion process of the fluid molecules at the gas-liquid-solid interface and simultaneously strengthens the transfer of CO2 between the graphite layers, allowing it to intercalate more effectively into the graphite layers. CO2 molecules entering the graphite layer undergo intense oscillations. The fluid shear force can be decomposed into a transverse force, which is perpendicular to the graphite sheet, and a force acting in the diffusion direction, which is parallel to the graphite sheet. The two forces work together to overcome the van der Waals forces between the graphite layers, causing the cross-section of the graphite sheet to shift relative to each other along the direction of the external force. Combined with the rapid decompression and expansion of supercritical CO2, graphite microsheets are then separated and prepared.

[0039] In one embodiment, in step 1, the mass ratio of graphite microflakes, graphite, and water is (0.5-1.5):19:(80-120).

[0040] In the ultrasonic treatment, the graphite microflakes of the present invention modify graphite, and the ultrasonic treatment time is, for example, 0.5h-2h, to disperse the graphite microflakes and graphite.

[0041] Then, the ultrasonically treated mixture is mixed with a tannic acid solution. The tannic acid solution is a solution formed by mixing tannic acid with a first solvent, which can be an organic solvent, an inorganic solvent, or a mixture thereof. The present invention does not particularly limit the first solvent, as long as it can dissolve the tannic acid; the dissolution of tannic acid can be promoted by methods such as heating. In one embodiment, the organic solvent is ethanol or acetone, and the inorganic solvent is water. In another embodiment, the ratio of the mass of tannic acid to the volume of the first solvent in the tannic acid solution is 1.5-4.5 g: 100 mL.

[0042] In one embodiment, in step 2, the mass ratio of graphite to tannic acid is 8:1-20:1. The ultrasonically treated mixture is mixed with the tannic acid solution, and stirring may be performed during the process. The mixing time can be 0.5-5 hours, for example, 1 hour, 2 hours, 3 hours, or 4 hours. In this way, tannic acid can coat graphite microflakes and graphite to form a double-layer structure.

[0043] In one embodiment, ultrasonically treated graphite flakes and a graphite mixture are added to a tannic acid solution to promote the completion of the coating.

[0044] After the ultrasonically treated mixture is mixed with the tannic acid solution, the solvent is removed, the mixture is dried, and then ground to obtain the graphite anode material precursor.

[0045] This invention does not specifically limit the method of solvent removal, such as rotary evaporation, and the pressure of rotary evaporation is, for example, atmospheric pressure or reduced pressure. This invention also does not specifically limit the particle size after grinding, and it can be selected as needed.

[0046] Finally, the graphite anode material precursor is carbonized to obtain the graphite anode material. In one embodiment, the carbonization temperature is 900-1300℃, the heating rate is 2-7℃ / min, and the carbonization process can be carried out under an inert gas, such as argon or nitrogen. In another embodiment, the graphite anode material precursor is first heated to 400-800℃ and held for a period of time, then heated to 900-1300℃ for carbonization.

[0047] In one embodiment, after the ultrasonically treated graphite microsheets and graphite mixture of the present invention are mixed with tannic acid solution, the solvent is removed to obtain a graphite anode material precursor. Then, the graphite anode material precursor is carbonized and ground to obtain the graphite anode material. That is, the grinding can be performed on the graphite anode material precursor or on the carbonized graphite anode material precursor; the present invention does not impose any particular limitation.

[0048] In this invention, rotary evaporation can be carried out in a rotary evaporator, which is a conventional device used in the art. In a specific embodiment of this invention, carbonization can be carried out in a high-temperature furnace, such as a high-temperature box furnace. Furthermore, this invention does not have special requirements for stirring, as long as dispersion can be achieved.

[0049] In one specific embodiment, the preparation method of the graphite anode material of the present invention includes the following steps:

[0050] 1. Mix 4.5g of tannic acid with 100ml of deionized water and stir at 80 degrees Celsius until fully dissolved to obtain solution A for later use. Sonicate 1g of graphite microflakes and 19g of graphite in 100ml of deionized water for half an hour, then pour it into solution A and stir for about one hour. After rotary evaporation and grinding, the graphite microflake modified graphite anode material precursor prepared by liquid phase method can be obtained.

[0051] 2. The obtained graphite micro-flake modified graphite anode material precursor is carbonized in a high-temperature furnace at a temperature of about 1300℃. After carbonization, it is then sieved to obtain the graphite micro-flake modified graphite anode material.

[0052] This invention utilizes the unique two-dimensional structure and high conductivity of highly conductive graphite microflakes, combined with tannic acid for carbon coating, to construct a graphite anode material modified with graphite microflakes and rich channel structure and multiple lithium storage sites, significantly improving the rate performance, fast charging performance, and cycle performance of lithium batteries. The introduction of graphite microflakes can greatly broaden the charge and discharge platform of graphite materials, increasing their effective capacity; tannic acid enables controllable and uniform coating of the material and forms a good conductive network after carbonization.

[0053] The technical solution of the present invention will be further described in detail below through specific embodiments. The graphite used in the following embodiments is the BFC-H graphite anode material produced by BTR Corporation.

[0054] Example 1

[0055] Graphite, graphite flakes, and water were mixed at a mass ratio of 0.95:0.05, and the water mass was 10 times the combined mass of graphite and graphite flakes. The mixture was sonicated for 1 hour. Then, a tannic acid solution (4.5% mass concentration) (based on tannic acid) was mixed with the above mixture (based on graphite flakes) at a mass ratio of 0.1:0.9. The solvent was removed, and the mixture was dried. Then, it was carbonized in a tube furnace (Ar atmosphere, flow rate 30 sccm) at a temperature of 5℃ / min to 350℃ for two hours, followed by a temperature increase to 900℃ at 5℃ / min. The carbonized material was then ground and sieved to obtain the graphite flake-modified graphite anode material.

[0056] The obtained negative electrode material was used to prepare lithium-ion battery electrodes as follows: The obtained graphite micro-sheet modified graphite negative electrode material was used as the active material, carbon black as the conductive agent, and PVDF as the binder. These were mixed evenly at a mass ratio of 95:1.5:3.5, and then N-methylpyrrolidone was used as a solvent to prepare the slurry. The slurry was coated onto a 12μm thick copper foil to form an electrode sheet, dried at 80℃ for 12 hours, and then rolled, sliced, and weighed for later use. A coin cell was assembled using a lithium metal sheet as the counter electrode, a Celgard 2300 membrane as the separator, and a 1mol / L LiPF6 / EC:EMC:DMC (volume ratio 1:1:1) electrolyte. The charge-discharge performance of the experimental battery was tested using a constant temperature charge-discharge tester from Shenzhen Xinwei Electronics Co., Ltd. The charge-discharge voltage range was 0.005-1.5V, and the charge-discharge current densities were 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C. The rate performance graph is shown below. Figure 1 As shown. Figure 1This diagram shows the rate performance of three materials: graphite micro-flake modified graphite prepared in Example 1 of this invention, commercial graphite anode material, and graphite raw material. The graphite micro-flake modified graphite prepared in Example 1 of this invention achieved a capacity of 362 mAh / g at a current density of 0.1C, and exhibited excellent performance at high rates, with the improvement becoming more pronounced as the charge / discharge current density increased. The graphite micro-flake modified graphite prepared in Example 1 of this invention still maintained a high capacity (70.9 mA hg) at a 3C rate. -1 Compared to commercial graphite anodes (39.7 mA hg) -1 ) and graphite raw materials (36.8mA hg) -1 The increased capacity is mainly attributed to the ultra-high conductivity of the graphite microplates and the significant role played by the uniform conductive network formed by tannins under high current density, which accelerates the transport of electrons and ions, thus leading to an increase in capacity.

[0057] Figure 2-4 The figures show the charge-discharge curves of the three materials at high rates. As shown, the discharge plateau of the commercial graphite anode and graphite raw material is short and indistinct at high current densities. This is because ions cannot be rapidly transported to the interlayer of graphite at high current densities, thus failing to complete the lithium intercalation process and therefore not exhibiting a good plateau curve. In contrast, the graphite microsheet-modified graphite anode material prepared in Example 1 of this invention has a distinct and longer charge-discharge plateau. This is attributed to the role of the stable carbon layer formed by the graphite microsheets and tannic acid in accelerating the rapid transport of ions and electrons.

[0058] Example 2

[0059] Mix 2g of tannic acid with 100ml of deionized water, heat at 80℃ and stir until fully dissolved, then set aside. Sonicate 1g of graphite microflakes and 19g of graphite in 100ml of deionized water for half an hour, then mix with the tannic acid solution and stir for about one hour. After rotary evaporation, the precursor of graphite microflake-modified graphite anode material prepared by the liquid-phase method is obtained. Then, carbonize in a tube furnace (Ar atmosphere, flow rate 30sccm) at 5℃ / min to 900℃. After grinding and sieving, the graphite microflake-modified graphite anode material prepared by the liquid-phase method is obtained.

[0060] Example 3

[0061] Mix 3g of tannic acid with 100ml of deionized water, heat at 80℃ and stir until fully dissolved, then set aside. Sonicate 1g of graphite microflakes and 19g of graphite in 100ml of deionized water for half an hour, then mix with the tannic acid solution and stir for about one hour. After rotary evaporation, the precursor of graphite microflake-modified graphite anode material prepared by the liquid-phase method is obtained. Then, carbonize in a tube furnace (Ar atmosphere, flow rate 30sccm) by heating to 400℃ at 2.5℃ / min, holding for one hour, then holding at 950℃ for two hours. After grinding and sieving, the graphite microflake-modified graphite anode material prepared by the liquid-phase method is obtained.

[0062] Example 4

[0063] Mix 3g of tannic acid with 100ml of deionized water, heat at 80℃ and stir until fully dissolved, then set aside. Sonicate 1g of graphite microflakes and 19g of graphite in 100ml of deionized water for half an hour, then mix with the tannic acid solution and stir for about one hour. After rotary evaporation, the precursor of the graphite microflake-modified graphite anode material prepared by the liquid-phase method is obtained. Then, carbonization is performed: first, the temperature is increased to 300℃ at 5℃ / min and held for one hour, then increased to 950℃ and held for two hours. After grinding and sieving, the graphite microflake-modified graphite anode material prepared by the liquid-phase method is obtained.

[0064] Example 5

[0065] 2.85 kg of graphite, 0.15 kg of graphite flakes, and 0.3 kg of tannic acid were premixed and placed in a mixer at approximately 600 rpm for about one hour. Then, the mixture was coated in a coating machine at approximately 100 rpm at a heating rate of 5 °C / min. The mixture was held at 300 °C for one hour, then at 600 °C for another hour, and finally allowed to cool. After cooling, the mixture was carbonized in a high-temperature furnace at a rate of 5 °C / min to 800 °C, and then at a rate of 2 °C / min to 1300 °C for two hours. Finally, the mixture was ground and sieved to obtain the graphite flake-modified graphite anode material prepared by the liquid-phase method.

[0066] This embodiment is for scaled-up production, achieving a liquid-phase coating effect by coating in a coating machine.

[0067] Example 6

[0068] 2.85 kg of graphite, 0.15 kg of graphite flakes, and 0.3 kg of tannic acid were premixed and placed in a mixer at approximately 600 rpm for about one hour. Then, the mixture was coated in a coating machine at approximately 100 rpm at a heating rate of 5 °C / min. The temperature was maintained at 300 °C for one hour, then increased to 650 °C for another hour, and finally allowed to cool. After cooling, the mixture was carbonized in a high-temperature furnace at a rate of 5 °C / min to 800 °C, and then at a rate of 2 °C / min to 1100 °C for two hours. Finally, the mixture was ground and sieved to obtain the graphite flake-modified graphite anode material.

[0069] Example 7

[0070] 2.85 kg of graphite, 0.15 kg of graphite flakes, and 0.3 kg of tannic acid were premixed and placed in a mixer at approximately 600 rpm for about one hour. Then, the mixture was coated in a coating machine at approximately 100 rpm at a heating rate of 5 °C / min. The mixture was held at 300 °C for one hour, then at 600 °C for another hour, and finally allowed to cool. After cooling, the mixture was carbonized in a high-temperature furnace at a rate of 5 °C / min to 800 °C, and then at a rate of 2 °C / min to 900 °C for two hours. Finally, the mixture was ground and sieved to obtain the graphite flake-modified graphite anode material.

[0071] Example 8

[0072] 2.94 kg of graphite, 0.06 kg of graphite flakes, and 0.3 kg of tannic acid were premixed and placed in a mixer at approximately 600 rpm for about one hour. Then, the mixture was coated in a coating machine at approximately 100 rpm at a heating rate of 5 °C / min. The mixture was held at 300 °C for one hour, then at 600 °C for another hour, and finally allowed to cool. After cooling, the mixture was carbonized in a high-temperature furnace at a rate of 5 °C / min to 800 °C, and then at a rate of 2 °C / min to 1300 °C for two hours. Finally, the mixture was ground and sieved to obtain the graphite flake-modified graphite anode material.

[0073] Example 9

[0074] 2.94 kg of graphite, 0.06 kg of graphite flakes, and 0.3 kg of tannic acid were premixed and placed in a mixer at approximately 600 rpm for about one hour. Then, the mixture was coated in a coating machine at approximately 100 rpm at a heating rate of 5 °C / min. The mixture was held at 300 °C for one hour, then at 600 °C for another hour, and finally allowed to cool. After cooling, the mixture was carbonized in a high-temperature furnace at a rate of 5 °C / min to 800 °C, and then at a rate of 2 °C / min to 1100 °C for two hours. Finally, the mixture was ground and sieved to obtain the graphite flake-modified graphite anode material.

[0075] Example 10

[0076] 2.94 kg of graphite, 0.06 kg of graphite flakes, and 0.3 kg of tannic acid were premixed and placed in a mixer at approximately 600 rpm for about one hour. Then, the mixture was coated in a coating machine at approximately 100 rpm at a heating rate of 5 °C / min. The mixture was held at 300 °C for one hour, then at 600 °C for another hour, and finally allowed to cool. After cooling, the mixture was carbonized in a high-temperature furnace at a rate of 5 °C / min to 800 °C, and then at a rate of 2 °C / min to 900 °C for two hours. Finally, the mixture was ground and sieved to obtain the graphite flake-modified graphite anode material.

[0077] Comparative Example 1

[0078] In this comparative example, the graphite anode material is not modified, and the graphite powder is used directly as the anode material.

[0079] Lithium-ion battery electrodes were prepared using graphite powder as the active material, carbon black as the conductive agent, and PVDF as the binder. These were mixed uniformly at a mass ratio of 95:1.5:3.5, and then a slurry was prepared using N-methylpyrrolidone as the solvent. The slurry was coated onto a 12 μm thick copper foil to form an electrode sheet, which was dried at 80°C for 12 hours. After rolling, slicing, and weighing, the electrode was ready for use. A coin cell was assembled using a lithium metal sheet as the counter electrode, a Celgard 2300 membrane as the separator, and a 1 mol / L LiPF6 / EC:EMC:DMC (volume ratio 1:1:1) electrolyte.

[0080] Comparative Example 2

[0081] The comparative sample did not have the graphite coated.

[0082] Graphite and graphite flakes were mixed at a mass ratio of 0.95:0.05, then ultrasonically dispersed in water at ten times their mass. After filtration and drying, the mixture was heated to 350°C at 5°C / min in a tube furnace (Ar atmosphere, flow rate 30 sccm) and held for two hours. The temperature was then increased to 900°C at 5°C / min for carbonization. The carbonized material was then ground and sieved to obtain the graphite flake-modified graphite anode material.

[0083] Comparative Example 3

[0084] Take 9g of graphite and 1g of commercially coated pitch (the coating pitch used is KELOUDE Pitch-A (MA-EN-OT-06011Y)). Dissolve the pitch in 100ml of tetrahydrofuran solution and stir at 500 rpm for one hour. Then, pour the graphite material into the pitch solution, ultrasonically disperse for 20 minutes, and continue stirring for one hour. After filtration and drying, heat the material in a tube furnace (Ar atmosphere, flow rate 30 sccm) at 5℃ / min to 350℃ and hold for two hours. Then, heat the material at 5℃ / min to 900℃ for carbonization. Finally, grind and sieve the carbonized material to obtain the pitch-coated graphite anode material.

[0085] The graphite anode materials obtained in each embodiment and comparative example were used to prepare batteries according to the method in Example 1. The battery performance is shown in Table 1.

[0086] Table 1. Performance of batteries prepared using graphite anode materials in each embodiment and comparative example.

[0087]

[0088]

[0089] Figure 5 The image shows a scanning electron microscope (SEM) image of the graphite microflakes modified with tannic acid coating prepared in Example 1. The graphite surface becomes glossy, and the graphite microflakes are well attached to the graphite surface. Figure 6 The electron microscope (SEM) image of the uncoated graphite flakes-modified graphite in Comparative Example 2 clearly shows the layered structure of the graphite. Although graphite flakes are also attached to its surface, due to the lack of tannic acid binding effect, the number and area of ​​graphite flakes are significantly less than those in the graphite flakes-modified graphite material of Example 1. Therefore, the material in Comparative Example 2, lacking a carbon layer coating, not only fails to prevent solvent co-intercalation in the graphite material but also fails to effectively fix the graphite flakes to the graphite surface, both of which are detrimental to improving material performance.

[0090] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a graphite anode material, characterized in that, Includes the following steps: Step 1: Mix graphite flakes, graphite, and water, and then sonicate. Step 2: Mix the mixture obtained in Step 1 with a tannic acid solution, and then remove the solvent to obtain a graphite anode material precursor; Step 3: Carbonize the graphite anode material precursor to obtain the graphite anode material.

2. The method for preparing the graphite anode material according to claim 1, characterized in that, In step 1, the mass ratio of graphite flakes, graphite and water is (0.5-1.5):19:(80-120); the graphite is expanded graphite powder or flake graphite.

3. The method for preparing the graphite anode material according to claim 1, characterized in that, The ultrasonic treatment time is 0.5h-2h.

4. The method for preparing the graphite anode material according to claim 1, characterized in that, The tannic acid solution is a solution formed by mixing tannic acid with a first solvent, wherein the first solvent is selected from organic solvents and inorganic solvents.

5. The method for preparing the graphite anode material according to claim 4, characterized in that, The organic solvent is ethanol or acetone; the inorganic solvent is water; the ratio of the mass of tannic acid to the volume of the first solvent in the tannic acid solution is 1.5-4.5 g: 100 mL.

6. The method for preparing the graphite anode material according to claim 1, characterized in that, The mass ratio of graphite to tannic acid is 8:1-20:

1.

7. The method for preparing the graphite anode material according to claim 1, characterized in that, Step 2 involves mixing for 0.5-5 hours, with stirring during the process.

8. The method for preparing the graphite anode material according to claim 1, characterized in that, The carbonization temperature is 900-1300℃, and the heating rate is 2-7℃ / min.

9. The method for preparing the graphite anode material according to claim 8, characterized in that, The graphite anode material precursor is first heated to 400-800℃ and held for a period of time, and then heated to the carbonization temperature for carbonization.

10. The graphite anode material obtained by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Low-cost long-cycle graphite negative electrode material, preparation method and application thereof

    CN113526956A

  • Fast charge graphite negative electrode material and preparation method thereof

    CN107601490A

  • High-capacity graphite negative electrode material and preparation method thereof, lithium ion battery and electric equipment

    CN117832444A